ANALYZING THE PATHWAYS OF COOPERATION BETWEEN CHINA AND UZBEKISTAN IN HIGHER EDUCATION - Xuemei, Wang; Rui , Wang; Duisenbay , K. (Journal of Oriental Studies, 2024)
The article deals with the writing of central Asia as an important bridge for China to unleash its influence on the West and to realize connectivity with European countries. Developing cooperation and maintaining close contact with Central Asia is one of the issues that China needs to address urgently. Uzbekistan is an important country in Central Asia. China is Uzbekistan’s largest trading partner, and the enhancement of cooperation between China and Uzbekistan is the result of mutual choices. Uzbekistan is carrying out a new round of education reform, it is of great practical significance to seize the opportunity to expand China-Uzbekistan higher educational cooperation. This paper will focus on the theme of higher education cooperation, discuss the current situation of higher education in Uzbekistan, and through the comparative analysis of Uzbekistan’s higher education cooperation with Russia, the United States, the European Union and Turkey, analyzes the ways of China-Uzbekistan higher educational cooperation at the macro and micro levels, including the establishment of private universities and university branch campuses. Keywords: Uzbekistan, China-Uzbekistan cooperation, higher education cooperations